2001
DOI: 10.1046/j.1468-8123.2001.11001.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pore size on cementation in porous rocks

Abstract: Halite cementation in porous sandstone from the Lower Triassic Bunter Formation in North-West Germany has been studied using measurements of porosity and permeability, before and after salt extraction, as well as from petrographic observations. The results show that in cemented sandstones there is a clear tendency for the larger pores to be halite-®lled while the smaller pores, which are responsible for the residual porosity, are left empty. Observations on cemented`pin-stripe' aeolian sandstones, in which lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(116 citation statements)
references
References 20 publications
1
112
1
2
Order By: Relevance
“…The volume influence on the effective solubility leads to supersaturation of the phase components in the solution; such an effect has been observed in porous sedimentary rocks (Emmanuel et al 2010, Putnis & Mauthe 2001 and in small pores in migmatites (Holness & Sawyer 2008). Because the solution is supersaturated, high undercooling is needed for crystallization to occur (Bigg 1953, Putnis & Mauthe 2001, Holness & Sawyer 2008.…”
Section: Why Are the Small Droplets More Undercooled?mentioning
confidence: 99%
See 1 more Smart Citation
“…The volume influence on the effective solubility leads to supersaturation of the phase components in the solution; such an effect has been observed in porous sedimentary rocks (Emmanuel et al 2010, Putnis & Mauthe 2001 and in small pores in migmatites (Holness & Sawyer 2008). Because the solution is supersaturated, high undercooling is needed for crystallization to occur (Bigg 1953, Putnis & Mauthe 2001, Holness & Sawyer 2008.…”
Section: Why Are the Small Droplets More Undercooled?mentioning
confidence: 99%
“…Quartz crystallization in sandstone does not occur in pores smaller than 10 µm (Emmanuel et al 2010). Putnis & Mauthe (2001) argued that supersaturation occurs if pore size is around 1 µm and does not occur for pores larger than 100 µm. Bigg (1953) observed that a water droplet of 10 µm could crystallize at -31 °C, sustaining high undercooling.…”
Section: Why Are the Small Droplets More Undercooled?mentioning
confidence: 99%
“…In general, equilibrium and nonequilibrium effects favour growth in large pores rather than in small pores. This has been observed for halite cemented sandstones (Putnis and Mauthe, 2001), for quartz cementation between stylolites in sandstone (Emmanuel et al, 2010), for gas hydrate (clathrate) growth in sediments (Rempel, 2011) or during precipitation of weathering products in porous andesite (Section 8.3 and Jamtveit et al, 2011).…”
Section: Pore Size Effectsmentioning
confidence: 83%
“…These salts generate disorders which are studied since the the 19th century (Turner, 1833). The constraints exerted by salts in the course of growth on the walls of the porous network of the rocks (Scherer 2004, Putnis andMauthe, 2001) can in the long term create and/or to widen cracks in the rocks.…”
Section: Fig 4: Damage Salt Develops As Encrustation Coveringmentioning
confidence: 99%